Dampak Artificial Financial Intelligence dalam Fintech Payments Terhadap Kinerja Keuangan Perbankan Indonesia: A Sytematic Literatur Review - Zulmedia (Jurnal Ilmiah Raflesia Akuntansi, 2025)
The development of artificial intelligence (AI) in fintech payments has significantly changed the financial landscape, presenting new opportunities and challenges for the banking industry. The purpose of this study is to analyze the impact of Fintech on the financial performance of banks listed on the IDX in Indonesia. The research method used is systematic literature review (SLR). SLR: This method is used to examine research published in journals within a particular field of research. It involves assessing the results of reviews conducted on a particular topic. In its study, SLR concluded that fintech adoption can have a positive impact on sustainable financial performance. One of these is the utilization of digital databases, internet banking (e-banking), mobile banking (m-banking) and digital ATMs. Accounts, etc.